REPUDIASI DALAM PEMENUHAN PRESTASI KONTRAK PENGADAAN BARANG/JASA PEMERINTAH - Chrestella Chrestella (Universitas Borneo Tarakan, 2021)
Abstract Government goods/services is never free from contracts. The contract is the basis of every action / achievement carried out both by the Government as the user of the goods / services and the Provider as the provider of the goods / services. In the process of running a contract is very prone to conflict / dispute between the parties. On average, contract conflicts up to contract disputes take place after the contract expires so that they can be carried out through courts or alternative dispute resolution institutions stipulated in the law. However, teh main point is this study is the contract conflict that has not been a contract dispute because the contract has not ended (the periode of contract execution) or the contract has not started (pre-contract). Can it be called a default if the contract has not been completed and there are parties who want to cancel the contract? Do the principles of goodfaith and balance apply to contracts where one of the parties is the government?Based on this, the following matters will be examined: 1) The principle of good faith in the government through contract repudiation to prevent breach of contract; 2) The principle of balance in the implementation of contract repudiation of government goods/service procurement. The research method used a normative juridical method with statutory and conceptual approaches. From the results of the study, it was concluded that in the case of the Government with the principle of good faith and proportional balance of contracts through Repudiation efforts trying to prevent harmful things such as defaults when the Government considers that the contract cannot be continued. The value of good faith as the most fundamental basis coupled with balance values in accordance with its portion or the so-called proportional principle must really be the most serious concern in making contracts not only to safeguard the rights and obligations of the parties but more importantly to achieve the purpose of the contract that is the fulfillment of government goods / services. Keywords : Repudiation, governement, contract, good faith, proportional.